The effect of prenatal gentle yoga combined with dhikr therapy on the level of anxiety in pregnant women - Samsinar, Samsinar; Warlinda; Rahmalia Dahman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Anxiety in pregnant women is a common problem and can have negative impacts on maternal and fetal health. Women experience anxiety during pregnancy which can increase the risk of complications such as postpartum depression, premature birth, and impaired infant development. Non-pharmacological interventions such as prenatal gentle yoga and dhikr therapy have been shown to be effective separately in reducing anxiety levels. This study aims to analyze the effect of the combination of the two interventions on the level of anxiety in pregnant women. This study used a quantitative method with a pre-experimental design ( one group pretest and posttest design ) without a control group. The study was conducted in June-July 2024 in the working area of the UPTD Bara Permai Health Center, Palopo City. The sample consisted of 26 pregnant women in the second and third trimesters who were selected using the accidental sampling technique. The intervention was a combination of prenatal gentle yoga and dhikr therapy for four weeks. The instrument used was the Perinatal Anxiety Screening Scale (PASS) to measure anxiety levels before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test . The average level of anxiety before the intervention was 28.69 (SD=7.504) and decreased to 20.81 (SD=8.551) after the intervention. The results of the statistical test showed a significant effect (p=0.000) on the level of anxiety of pregnant women before and after being given a combination of prenatal gentle yoga and dhikr therapy intervention. The combination of prenatal gentle yoga and dhikr therapy has been proven effective in reducing anxiety levels in pregnant women. This intervention can be used as an alternative non-pharmacological approach that is safe, easy to implement, and low-cost to overcome anxiety during pregnancy, especially in the second and third trimesters approaching delivery.